CLINICAL PHARMACY IN GALLE SRI LANKA, COLLABORATION AND FRIENDSHIP - Morrissey, Hana; Zawahir, Shukry; Hettihewa, Sujeewa; Ball, Patrick (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Pharmacy undergraduate courses in Ruhuna, while is more practice focus than many of the other courses in Sri Lanka, it is still missing clinical pharmacy elements. Collaboration between academic staff from Ruhuna University and two international clinical pharmacy academics was established in 2014. The aim of this paper is to report on a clinical pharmacy training program, delivered by the international academics and supported by the Sri Lankan academics to pharmacy students in 2015-2016. After short conceptualisation lecture on each topic, there was a workshop which was structured as team case-based learning progressive case studies. Topics included mental health, pharmacokinetics, interpreting laboratory results, parenteral drug compatibility, special hospital compounding and medication review, of which all were assessed in the final examination. Student found team based learning to be engaging and enabled them to independently and critically think in a safe environment and preferable over the traditional lectures.